O papel dos receptores do tipo Toll (TLRs) na infecção pelo Schistosoma mansoni - Fernanda do Valle Duraes (2010)
ABSTRACTSchistosomiais is a chronic helminthic infection and remains as an important morbidity factor in tropical endemic areas such as Brazil. Toll-like receptors (TLRs) play an important role in the innate recognition of pathogens by Dendritic cells (DCs) and in the induction of immune responses. Although it is clear that TLR2, TLR3 and TLR4 can recognize different Schistosoma components in vitro, little is known regarding the role of these receptors in vivo. To characterize the innate immune response during Schistosoma infection, WT (C57BL/6) and MyD88-, TLR2- and TLR4 deficient mice were infected with 30 cercariae. Parasitological parameters, such as the number of worms recovered and the number of eggs in the liver, as well as pathological and immunological parameters were evaluated. Even though the differences between WT and KO mice in terms of worm burden were not significant, TLR2 KO mice displayed reduced fecundity, resulting is less eggs trapped in the liver. However, major differences were seen regarding host immune responses. The lack of MyD88 and TLR2 resulted in smaller granulomas followed by reduced production of CCL11 in the hepatic tissue of these mice. Furthermore, cells from infected MyD88 KO mice also produced significantly less IL-5 than their WT controls, both in the liver tissue and in spleen cells upon restimulation with Schistosoma egg antigen (SEA), indicating diminished Th2 response. Further, Schistosoma mansoni larvae is the first and the most susceptible parasite life stage to interact with the host immune system. Therefore, the role of the innate immune system was evaluated in an in vitro model of DC activation by schistosomula tegument (Smteg). Smteg was able to activate DCs to produce IL-12p40, TNF- and also to up-regulate the co-stimulatory molecules CD40 and CD86. Moreover, using DCs derived from MyD88-, TLR2- and TLR4 deficient mice we have shown that the ability of Smteg to activate DCs in vitro involves MyD88 signaling pathways and TLR4/Smteg interaction. Together, these data indicate that the innate immune system is involved in the initial recognition of Schistosoma components both in vitro and in vivo. These interactions play an important role in dictating the outcome of pathological and immunological changes resulting from the infection.